2017
DOI: 10.1016/j.jcde.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of the leakage flow in guide vanes with different hydrofoils

Abstract: Clearance gaps between guide vanes and cover plates of Francis turbines tend to increase in size due to simultaneous effect of secondary flow and erosion in sediment affected hydropower plants. The pressure difference between the two sides of the guide vane induces leakage flow through the gap. This flow enters into the suction side with high acceleration, disturbing the primary flow and causing more erosion and losses in downstream turbine components. A cascade rig containing a single guide vane passage has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…However, the vortex seems to dissociate gradually while it travels from NACA 4412 GV profile with all clearance gap. The flow field depicts similar findings in the past experiment with single GV test rig in the case of NACA 0012 hydrofoil (Thapa, Dahlhaug, and Thapa, 2017 a, b).…”
Section: Leakage Flow From Gvsupporting
confidence: 82%
See 3 more Smart Citations
“…However, the vortex seems to dissociate gradually while it travels from NACA 4412 GV profile with all clearance gap. The flow field depicts similar findings in the past experiment with single GV test rig in the case of NACA 0012 hydrofoil (Thapa, Dahlhaug, and Thapa, 2017 a, b).…”
Section: Leakage Flow From Gvsupporting
confidence: 82%
“…This equation gives good agreement between masstransfer simulations with experimental data (Chitrakar, Thapa, Dahlhaug, and Neopane, 2017). The sensitivity study of the turbulence models SST, BSL and Omega RS suggests SST model be suitable for the current case too (Chitrakar, Thapa, Dahlhaug, and Neopane, 2016).…”
Section: Governing Equations and Turbulence Modelmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly, for the design of the guide vanes, it is found that the change in the guide vane's hydrofoil profiles could minimize the erosion in runner and guide vanes at some operating conditions [24]. The hydrofoils are usually standard profiles such as NACA.…”
Section: Sedimentation Engineering 20mentioning
confidence: 99%